2014
DOI: 10.1088/0004-6256/148/4/63
|View full text |Cite
|
Sign up to set email alerts
|

Follow Up Observations of SDSS and CRTS Candidate Cataclysmic Variables

Abstract: We present photometry of 11 and spectroscopy of 35 potential cataclysmic variables from the Sloan Digital Sky Survey, the Catalina Real-Time Transient Survey and vsnet-alerts. The photometry results include quasi-periodic oscillations during the decline of V1363 Cyg, nightly accretion changes in the likely Polar (AM Herculis binary) SDSS J1344+20, eclipses in SDSS J2141+05 with an orbital period of 76±2 min, and possible eclipses in SDSS J2158+09 at an orbital period near 100 min. Time-resolved spectra reveal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
5
20
1
Order By: Relevance
“…They are broadly consistent with previous studies in the field (e.g., Szkody et al 2002Szkody et al , 2003Szkody et al , 2004Szkody et al , 2005Szkody et al , 2006Szkody et al , 2007Szkody et al , 2009Szkody et al , 2011Szkody et al , 2014Thorstensen & Skinner 2012;Thorstensen et al 2016;Breedt et al 2014;Woudt et al 2012;Coppejans et al 2014).…”
Section: Observational Characteris-tics Of Magnetic Cvssupporting
confidence: 92%
See 1 more Smart Citation
“…They are broadly consistent with previous studies in the field (e.g., Szkody et al 2002Szkody et al , 2003Szkody et al , 2004Szkody et al , 2005Szkody et al , 2006Szkody et al , 2007Szkody et al , 2009Szkody et al , 2011Szkody et al , 2014Thorstensen & Skinner 2012;Thorstensen et al 2016;Breedt et al 2014;Woudt et al 2012;Coppejans et al 2014).…”
Section: Observational Characteris-tics Of Magnetic Cvssupporting
confidence: 92%
“…Another outburst was recorded by ASAS at 16.39 mag on 2013 August 27 (Ohshima 2013). Szkody et al (2014) present a spectrum with strong emission Balmer lines obtained on 2013 September 3 and classify the object as a dwarf nova, possibly eclipsing due to the dispersion of the CRTS quiescent light curve. This spectrum was taken in a state brighter than the quiescent flux in the CRTS light curve.…”
Section: Css0104-03 (Css091009:010412-031341)mentioning
confidence: 98%
“…Our mean spectrum ( Fig. 1) shows strong emission on a blue continuum, similar to that published by Szkody et al (2014) but covering a greater spectral range. Hα has an equivalent width (EW 2 ) of 80Å, and a full width at half-maximum (FWHM) of 1200 km s −1 .…”
Section: Css0015+26supporting
confidence: 84%
“…Denisenko (2013;Vsnet-alert 16457) monitored the source more closely and suggested that it might be an active polar, or AM Her star. Szkody et al (2014) obtained spectroscopy on one night, indicating an orbital period near 103 min, which was corroborated by two humps seen in 2.8 hours of time series photometry. Because the HeII λ4686 line was absent, and the velocity amplitude modest, they rejected the polar classification.…”
Section: Css0143+26supporting
confidence: 54%
“…The system name and orbital period are shown in the plot. Only the later five runs (S8533 -S8545) are shown for ASASSN-14eq.4.5 CSS 0353-03 (CSS111231:035318-034847)After its discovery on 2011 Dec 31(Drake et al 2009),Szkody et al (2014) obtained a spectra of CSS 0353-03 during the 2013 Jan outburst. The spectrum showed a flat blue continuum.…”
mentioning
confidence: 99%